A large aneurysmal bone cyst of the rib. (May 2019) - Kumar, Vikas; Singh, Rana Sandip; Rawat, Sanjib; Gupta, Kirti; Parikh, Mayur
An aneurysmal bone cyst is a very rare benign tumor of the ribs. It mainly involves the long bones and vertebrae, and requires histopathological examination for definitive diagnosis. We present a case of large aneurysmal bone cyst of the left 6th rib in young adult male. The diagnosis of aneurysmal bone cyst should be kept in mind in young patients presenting with an expansile lytic lesion of the rib, because it has an excellent outcome after complete surgical resection.